Effect of Moisture Content on some Engineering Properties of African Mahogany (Afzelia Africana) Seed - Aviara, N. A.; Ekaso Jr, S.; Nwanja, O. U. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Some engineering properties of Afzelia africana, namely axial dimensions, one thousand seed mass, surface area, particle density, bulk density, porosity, angle of repose, static and kinetic coefficients of friction, coefficient of restitution and specific heat were determined as a function of moisture content in the moisture range of 6.1 – 32.3% (d.b). Results showed that in the above moisture range, major, intermediate and minor axial dimensions of the seed increased from 25.4 – 26.2mm, 13.2 – 13.95mm and 10.2 – 11.2mm, respectively. One thousand seed mass, surface area, particle density, porosity, angle of repose, static coefficient of friction, kinetic coefficient of friction and specific heat capacity of the seeds all increased with increase in moisture content. Seed bulk density decreased with increase in moisture content and coefficient of restitution decreased as drop height and moisture content increased. The relationship existing between the engineering properties and seed moisture content, established using regression analysis showed high coefficient of determination. These properties would be useful in the design of Afzelia africana seed handling, storage and processing equipment.